Methodology of organization and performance of fiscal inspection in Romania - HURLOIU Lăcrămioara; HURLOIU Iulian (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Tax inspection is the activity aimed at verifying the legality and compliance of tax returns, the correctness and accuracy of fulfilling obligations in connection with the establishment of tax obligations by the taxpayer / payer, compliance with tax and accounting legislation, verification or establishment, as appropriate, of tax bases and the related factual situations, establishing the differences of main fiscal obligations. The tax inspection is exercised on any person and entity, regardless of their form of organization, to taxpayers as well as to payers, meaning that person who, on behalf of the taxpayer, has the obligation to pay or withhold and pay or to pay, collect and pay, as appropriate, taxes, fees and social contributions. Fiscal inspection is exercised on the basis of the principles of independence, uniqueness, autonomy, hierarchy, territoriality and decentralization.